736 MicroRNA expression patterns in melanomas originating from gynecologic sites. (10th December 2020) - DiVincenzo, Mallory; Suarez-Kelly, Lorena; Moufawad, Maribelle; Ren, Casey; Barricklow, Zoe; Fadda, Paolo; Yu, Lianbo; Peters, Sarah; Gru, Alejandro; Carson, William
Abstract : Background: Melanomas originating from gynecologic sites (MOGS) are rare mucosal melanomas originating from the vulva, vagina, and cervix. MOGS are associated with a poor survival rate and limited therapeutic options, as patients often present an advanced disease stage. MiRNAs (miRs) are a class of small, non-coding RNA molecules composed of 21–23 nucleotides that control expression of target genes via post-transcriptional regulation and can exhibit dysregulated expression in cancer. Patterns of miR expression and their effects on disease progression have not yet been explored in the setting of MOGS. We hypothesize a unique miR expression profile exists in MOGS that can mediate disease progression via interaction with target genes. Methods: RNA was isolated from formalin fixed, paraffin embedded tissue samples of human vaginal and vulvar melanoma for comparison to normal adjacent vaginal mucosal tissue (NAT) and primary cutaneous melanoma (PCM), respectively. miR expression was then quantified using the NanoString human miRNA assay. Common experimentally validated gene targets of differentially expressed (DE) miRs were identified using miRNet, and pathway analysis was completed to examine potential downstream effects of dysregulated miR expression. Results: Comparison of miR expression in vaginal melanoma to NAT revealed 25 DE miRs (fold change > 1.5, p < 0.05), with 10 demonstrating a significant decrease in expression in vaginal melanoma tissue relative to NAT, including hsa-miR-145-5p, hsa-miR-99a-5p, and hsa-miR-1972, and 15 exhibiting a significant increase in expression including hsa-miR-17-5p, hsa-miR-19b-3p, hsa-miR-20a-5p, and hsa-miR-20b-5p. 45 DE miRs were identified between vulvar melanoma and PCM, among which 3 demonstrated a significant decrease in expression in vulvar melanoma including miR-200b-3p, miR-494-3p, and miR-200a-3p, and 44 demonstrated a significant increase in expression including miR-17-5p, miR-146a-5p, and miR-19b-3p (fold change > 2, p < 0.01). Among these DE miRs, both miR-17-5p and miR-146a-5p have recently been experimentally validated as direct or indirect regulators of PD-L1 expression in melanoma. Pathway analysis for DE miRs in vaginal and vulvar melanoma revealed significant enrichment of 35 and 30 pathways, respectively, each including TGF-β signaling, for which 57 genes in the pathway are validated targets of 13 DE miRs in vaginal melanoma (p = 1.5e-12), and 59 genes in the pathway are validated targets of 17 DE miRs in vulvar melanoma (p = 2.4e-13). Conclusions: The results of this study support miRNAs as important potential regulators of gene expression in vaginal and vulvar melanomas that can contribute to tumor progression, tumor immunogenicity, and response to current immunotherapies. Ethics Approval: This study was approved by the Ohio State University Institutional Review Board, approval #2007C0015.